Multilevel Inverter Fed Switched Reluctance Motors (SRMs): 6/4, 8/6 and 10/8 SRM Geometric Types - Nabil Farah; M.H.N. Talib; Jurifa Lazi; Majed Abo Ali; Z. Ibrahim (Institute of Advanced Engineering and Science, 2017)
Nowadays power electronics circuits are embedded to most of electrical application areas. This approached offers a great control mechanism with simple and easy circuit configuration. Switched Reluctance Motor (SRM) is one of the most recent apparatus which draws a great number of researchers’ interests. Previously several attempts are made to use the power converters as driver for SRM such as Voltage Source Inverter (VSI) and bridge converters. This paper presents an analysis study of three level inverter to control the SRM. The inverter is controlled using space vector modulation SVM. The aim of this paper is to report the use the multilevel inverter to be fed into the SRM. The implementation of the multilevel inverter is abl to reduce the Total Harmonics Distortion (THD). Performance comparison are made between the multilevel and previous power electronics circuits that applied to the SRM. The simulation results have been conducted by MATLAB/SIMULINK software.